2010
DOI: 10.1158/0008-5472.can-10-2858
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, a Red Wine Polyphenol, Suppresses Pancreatic Cancer by Inhibiting Leukotriene A4 Hydrolase

Abstract: The anticancer effects of red wine have attracted considerable attention. Resveratrol (3,5,4′-trihydroxy-trans-stilbene) is a well-known polyphenolic compound of red wine with cancer chemopreventive activity. However, the basis for this activity is unclear. We studied leukotriene A4 hydrolase (LTA4H) as a relevant target in pancreatic cancer. LTA4H knockdown limited the formation of leukotriene B4 (LTB4), the enzymatic product of LTA4H, and suppressed anchorage-independent growth of pancreatic cancer cells. An… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 38 publications
1
80
1
Order By: Relevance
“…Over the past couple of decades, after Jang et al [16] reported Res as a cancer chemopreventive agent, it has received tremendous attention. Recent studies have shown its anticancer effects on pancreatic carcinoma [17,18,19]. However, the mechanism has not been well known.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past couple of decades, after Jang et al [16] reported Res as a cancer chemopreventive agent, it has received tremendous attention. Recent studies have shown its anticancer effects on pancreatic carcinoma [17,18,19]. However, the mechanism has not been well known.…”
Section: Introductionmentioning
confidence: 99%
“…Scoring estimates the chemical interactions, such as binding strength and energy state, between the ligand and protein to assist in the in ranking the efficacy of the compound being scored (Nagarajan et al, 2009;Perez-Sanchez and Wenzel, 2011;Oi et al, 2010). From these approaches, several potential candidate phytochemicals that directly interact with target proteins can be identified in future for the development of effective drug against cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, resveratrol has been found to suppress proliferation and anchorage-independent growth of pancreatic cancer by inhibiting leukotriene B4 (LTB4) production and expression of the LTB4 receptor 1 (LTB4R1) [146]. It is remarkable that LTB4 is a hydrolysis product of the leukotriene A4 (LTA4), and the process is catalyzed by LTA4 hydrolase, a known target for prevention and therapy of cancers including PC [147].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is remarkable that LTB4 is a hydrolysis product of the leukotriene A4 (LTA4), and the process is catalyzed by LTA4 hydrolase, a known target for prevention and therapy of cancers including PC [147]. Resveratrol can directly bind to leukotriene A4 hydrolase (LTA-4H) and inhibit its activity and, therefore, LTB4 production [146].…”
Section: Accepted Manuscriptmentioning
confidence: 99%